Meningkatkan Keterampilan Literasi Siswa Melalui Pemahaman Literasi Digital pada Masa Pandemi Covid-19 - Siti Aisyah; Lilis Yuliati (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has had an impact on various sectors, one of which is the education sector. The learning system that was originally implemented face-to-face in schools is now being replaced with an online learning system. This is also one of the parents' complaints. One of them is in Petung Village, Bangsalsari District, Jember Regency, where children are less than optimal when studying at home. In addition, parents who do not understand digital technology find it difficult to provide assistance. KKN BTV 3 UNEJ students are here with the aim of providing an understanding of Digital Literacy to parents and children in learning at home. The main focus in this KKN activity is to provide understanding about Digital Literacy to parents and students. The implementation of the program is carried out in 4 stages, namely, Preparation, Socialization, Learning Education, Training, and Evaluation. The results achieved in this activity are an understanding of Digital Literacy for parents and can improve students' literacy skills, as well as effectiveness in learning activities at home.